Analysis of Effectiveness, Additional Employee Income (TPP), and Work Motivation on The Performance of State Civil Apparatus (ASN) With Work Discipline as A Moderating Variable at Medan City Health Service - Mutiari, Riri; Chaerul Rizky, M.; Nuzuliati, Nuzuliati (International Journal of Social Science, Education, Communication and Economics, 2024)
This study explores the impact of Effectiveness, Additional Employee Income (TPP), and Work Motivation on the performance of State Civil Apparatus (ASN) at the Medan City Health Service, with Discipline as a moderating variable. The quantitative method was employed with a population of 190 ASN employees, and a sample of 127 ASN. Data analysis was conducted using Structural Equation Modeling (SEM) with Smart Partial Least Squares (PLS) technique. The research findings indicate a positive and significant influence of Effectiveness, TPP, Work Motivation, and Work Discipline on the performance of ASN in the Medan City Health Service. Additionally, there is a positive and significant impact of Effectiveness, TPP, and Work Motivation on the performance of ASN moderated by Work Discipline. The conclusion drawn from this research is that Work Discipline has the most significant influence on the performance of ASN, while TPP has the least impact. Recommendations involve enhancing focus on developing Work Discipline to significantly improve employee performance. Despite TPP having the smallest impact, strategic considerations are still necessary in incentive management to maintain employee motivation.